The content of the insolvency agreement proposal: possible scenarios and prohibitions - Quijano González, Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
In the historical evolution of Insolvency Law, the agreement reached by the debtor and its creditors has fulfilled the main function of facilitating the preservation of the activity, generally business, affected by insolvency, although insolvency proceedings often led to the liquidation of the assets as an inevitable solution. In the Bankruptcy Law currently in force in Spain, after the reform of 2022, the agreement has acquired a flexibility in terms of its possible content that makes it especially useful for resolving insolvency situations that are being processed as bankruptcy proceedings, which does not prevent recognizing that the priority today is to anticipate the solution in the pre-bankruptcy or pre-insolvency phase through the most diverse restructuring techniques. This paper analyzes in particular the possible content of the insolvency agreement proposal in our legal system, with special attention both to the various types of possible scenarios (agreements with waiver and waiting, with additional proposals, with structural modifications), and to the set of prohibitions that constitute the limit of such content, either because they affect the credits, or because they actually imply a liquidation.